ANALYSIS OF PLEBANSKI-DEMIANSKI METRIC AND ITS COMPARISON WITH AXISYMMETRIC STATIONARY METRIC - FIKRI ASSAFARI (NIM : 20216004), ROSIKHUNA
The solution of Einstein's Field Equation in axissymmetric-stationary spacetime is generally represented by Kerr-Newman metric in Minkowski background and by Kerr-Newman-de Sitter in de Sitter background. More general representation of axisymmetric-stationary spacetime is represented by Plebanski-Demianski metric and constant Ricci scalar metric. These two metrics are obtained with different procedure. Kerr-Newman-de Sitter and constant Ricci scalar metric can be derived from Plebanski-Demianski metric with transformation and limiting procedure. From this procedure it can also be seen that the Plebanski-Demianski metric is more general than constant Ricci scalar metric. Further analysis of Plebanski-Demianski metric includes examining its Ricci scalar and its physical and coordinate singularity.